2022
DOI: 10.1107/s2059798322007318
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the acetylation mechanism of the Legionella effector VipF

Abstract: The pathogen Legionella pneumophila, which is the causative agent of Legionnaires' disease, secrets hundreds of effectors into host cells via its Dot/Icm secretion system to subvert host-cell pathways during pathogenesis. VipF, a conserved core effector among Legionella species, is a putative acetyltransferase, but its structure and catalytic mechanism remain unknown. Here, three crystal structures of VipF in complex with its cofactor acetyl-CoA and/or a substrate are reported. The two GNAT-like domains of Vip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 48 publications
3
3
1
Order By: Relevance
“…1F ). These results are in line with our structural analysis, indicating that only the C-terminal domain of the VipF effectors is responsible for observed in vitro acetyltransferase activity, which was also shown in a previous report of Lpg0103 ( 23 ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…1F ). These results are in line with our structural analysis, indicating that only the C-terminal domain of the VipF effectors is responsible for observed in vitro acetyltransferase activity, which was also shown in a previous report of Lpg0103 ( 23 ).…”
Section: Resultssupporting
confidence: 93%
“…Among tested substrates, we observed that Lha0223 activity was highest against chloramphenicol, in line with the general activity reported for L. pneumophila VipF/Lpg0103 ( Fig. 1B ) ( 22 , 23 ). However, Lha0223 also demonstrated strong activity against poly-lysine substrate suggesting that it can be active against peptide or protein targets.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations